Clinical associations of complement-activating collectins, collectin-10, collectin-11 and mannose-binding lectin in preterm neonates - Gajek, Gabriela; Hansen, Soren W. K.; Jarych, Dariusz; Kufelnicka-Babout, Maja; Świerzko, Anna S.; Kobiela, Paulina; Szala-Poździej, Agnieszka; Chojnacka, Karolina; Sobczuk, Katarzyna; Domżalska-Popadiuk, Iwona; Mazela, Jan; Kalinka, Jarosław; et al. (Frontiers in Immunology, 2024)
Introduction: Premature and low-birthweight infants are at especially high risk of perinatal complications, including impaired thermoregulation, infections and respiratory distress. Such adverse effects and the need for invasive procedures are associated with high mortality among preterms. This study focused on the influence of the innate immune system and tested the levels of collectins, collectin-10 (CL-10), collectin-11 (CL-11) and mannose-binding lectin (MBL) in preterm neonates.Methods: Cord blood was collected from 535 preterms (born at gestational age ≤37 weeks). COLEC10 and COLEC11 polymorphisms were analysed by real-time PCR and those of MBL2 by PCR/PCR-RFLP. The concentrations of collectins in sera from cord blood were determined with ELISA.Findings: Low concentrations of CL-10 in cord sera (<462 ng/ml corresponding to the 10 th percentile) were significantly associated with births at GA ≤32 weeks. Median levels of both CL-10 and CL-11 were significantly lower in preterms with very low birthweight (<1500 g), low Apgar 1' score and those who needed prolonged hospitalisation. Lower median CL-10 was also observed in fetal growth restriction cases. An important finding was the decreased concentrations of CL-10, CL- 11 and MBL in respiratory distress syndrome (RDS). For CL-10 and CL-11, that relationship was confined to infants born at GA ≥33 weeks and/or with body mass at birth ≥1500 g. Only CL-10 was found to influence susceptibility to early-onset infections. COLEC11 heterozygosity for the activitydecreasing polymorphism (rs7567833, +39618 A>G, His219Arg) was more common in preterm premature rupture of membranes (pPROM) cases, compared with corresponding reference groups. Furthermore, C/T or T/T genotypes at COLEC11 at rs3820897 (-9570 C>T) as well as MBL deficiency-associated MBL2 gene variants were more common in preterms diagnosed with RDS than among unaffected newborns.The complement-activating collectins investigated here could be important for maintaining homeostasis in preterm neonates. Despite similar structure and specificity, MBL, CL-10 and CL-11 manifest a different spectrum of clinical associations.